2019
DOI: 10.3329/bccj.v7i1.40765
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of safety of caesarean myomectomy: A prospective study

Abstract: Background: Uterine myomas are the most common benign tumour of female reproductive tract and the prevalence of myomas in pregnancy has been reported to be 2%to 5% . Myomectomy during cesarean section has traditionally been discouraged due to risk of intractable haemorrhage and fear of hysterectomy. But recently large scaled studies indicated that cesarean myomectomy could be safely performed in majority of cases without any serious or life threatening complications. Materials and Methods: This prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Consistently, in the studies of Sakinci et al (6) and Guler et al (7) , myomectomy added 15, 14 min to the CS duration. Morzak et al (8) and Nargis et al (9) reported a significant difference regarding the operation time and the hospital stay length In another similar study, the CS duration was only 4.94 minutes longer in the myomectomy group than it was in the nonmyomectomy group, which was not a significant difference (10) . Significant or not, all these findings reveal acceptable extensions, particularly when compared to performing a second operation to remove myomas that were not removed during CS.…”
Section: Discussionmentioning
confidence: 92%
“…Consistently, in the studies of Sakinci et al (6) and Guler et al (7) , myomectomy added 15, 14 min to the CS duration. Morzak et al (8) and Nargis et al (9) reported a significant difference regarding the operation time and the hospital stay length In another similar study, the CS duration was only 4.94 minutes longer in the myomectomy group than it was in the nonmyomectomy group, which was not a significant difference (10) . Significant or not, all these findings reveal acceptable extensions, particularly when compared to performing a second operation to remove myomas that were not removed during CS.…”
Section: Discussionmentioning
confidence: 92%
“…These findings are in accordance with the study conducted by Hassiakos et al and Nargis et al where the majority of patients were having sub serosal myomas. 13,14 In the study by Adesiyun et al, a total of 46 fibroids were removed in the 22 patients, of them 52.2% were subserous, 34.8% were intramural and 6 were submucous, 69.9% fibroids were between 6-10cms size. 15 The most common location of fibroid being corpus anterior (64%) with 14% being posteriorly located fibroid.…”
Section: Discussionmentioning
confidence: 99%